Aseneth’s Gaze Turns Swords into Dust - Jovanovic, Ljubica O. (Journal for the study of the pseudepigrapha, 2011)
This article argues that Aseneth’s prayer and the divine response in Joseph and Aseneth 27.8 are later hagiological interpolations that reflect the concerns of Eastern Orthodox Christianity. In the Hellenistic version of Joseph and Aseneth , the heroine performs her miraculous rescue using only her glance: the power accorded her sight fully corresponds with predominant theories of antiquity on the divine nature of light. Hellenistic audiences were familiar with the concept of emission of energy through the human eye, maintained by Plato, Euclid and Ptolomy, which under certain circumstances and divine favor could perform miracles. Hagiographically inspired editors, insisting that the miracle related not to Aseneth’s powerful gaze but to her piety and the divine response, added the lines and so shifted the focus from the powerful gaze to the power of piety.